The health care needs of the physically disabled patient in a home-based care environment: Implications for the training of ancillary health care workers - Karien Jooste; Mary Chabeli; Monica Springe (AOSIS, 2010)
According to existing literature, ancillary health care workers (AHCWs) often do not meet the health care needs of patients with physical disabilities (physically disabled patients) in a homebased environment, because of inadequate training programmes. The purpose of this research study was to explore the health care needs of physically disabled patients in long-term, home-based care in the northern suburbs of Johannesburg and, based on results, to offer recommendations for the training of AHCWs. Qualitative, exploratory, descriptive and contextual means were employed in data collection and analysis. The population consisted of eight physically disabled participants who employed an AHCW to assist them with their long-term home care. Purposive sampling was used with subsequent snowballing to identify further participants for the study. Individual interviews were conducted, where participants had to answer the questions (1)'What are your health care needs?' and(2) 'How should these be met?' Data saturation was ensured, after which Tesch's method of data analysis was followed. Three categories of health care needs were identified (1) physical health care needs, (2) interpersonal relationship needs and (3) social needs, and 12 themes were derived from these categories. These categories of health care needs should be addressed in the training of AHCWs.From the themes, recommendations were described for the training of AHCWs on the health care needs of the home-based physically disabled patients. The AHCW should assist in the adaptation of the environment to the patient's individual needs, and should use knowledge and critical thinking skills to ensure a patient-centred care setting. Opsomming Volgens die literatuur kan assistentgesondheidsorgwerkers (AGWs), as gevolg van ontoereikende opleiding, nie altyd aan die behoeftes van fisies gestremde pasiënte in 'n tuisopset voldoen nie.Die doel van hierdie navorsingstudie was om die gesondheidsorgbehoeftes van langtermyn,tuisgebaseerde fisies gestremde pasiënte in die noordelike voorstede van Johannesburg te verken en te beskryf, en om hieruit aanbevelings vir die opleiding van AGWs voor te stel. Kwalitatiewe,verkennende, beskrywende en kontekstuele metodes is gebruik om die data in te samel en die analise te doen. Die studiepopulasie het uit agt fisies gestremde deelnemers bestaan wat 'n AGW aangestel het om hulle met hul langtermyntuisversorging by te staan. Doelbewuste steekproefneming met die daaropvolgendesneeubalmetode is gebruik om verdere deelnemers vir die studie te identifiseer.Individuele onderhoude is gevoer waartydens deelnemers die volgende vrae moes beantwoord (1)'Wat is jou gesondheidsorgbehoeftes?' en (2) 'Hoe behoort hieraan voldoen te word?' Datasaturasie is verseker, waarna Tesch se data-analisemetode gevolg is. Drie kategorieë van gesondheidsorgbehoeftes is geïdentifiseer (1) fisiese gesondheidsorgbehoeftes, (2) interpersoonlike verhoudingsbehoeftes en (3)sosiale behoeftes, en 12 temas is van hierdie kategorieë afgelei. Hierdie gesondheidsorgkategorieë behoort aandag tydens die opleiding van AGWs te kry. Aan die hand van die temas is aanbevelings gemaak vir die opleiding van AGWs in tuisgebaseerde sorg van fisies gestremde pasiënte. AGWs behoort ondersteuning te bied om die omgewing by die individuele behoeftes van die pasiënt aan te pas, en moet hul kennis en kritiese denkvaardighede kan toepas om ŉ pasiëntgesentreerde omgewing te verseker.